1998
DOI: 10.1063/1.121551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhomogeneous oxygen content in (La,Gd)0.7Ca0.3MnO3+δ perovskites

Abstract: Magnetoresistance properties of compounds with the same formula La0.7−xGdxCa0.3MnO3+δ (x=0, 0.04) but synthesized by the solid-state reaction method from different starting materials are studied. Nearly stoichiometric compounds are obtained when La(OH)3 is used for sample preparation. However, under the same condition, La2O3 causes considerable oxygen deficiency in resulting samples, characterized by a broad metal–semiconductor transition far below the magnetic transition. Inhomogeneous distribution of the oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
20
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 17 publications
7
20
0
Order By: Relevance
“…Gebhardt et al [28] have shown that the chemical inhomogeneity is the origin of the double peak in resistivity behavior of their samples. Sun et al [29] have shown that the oxygenation inhomogeneity leads to a double peak behavior. In these cases, the compositional disorder occurs in the scale of the whole sample and not in each grain as in the case of small grain size samples.…”
Section: Resultsmentioning
confidence: 98%
“…Gebhardt et al [28] have shown that the chemical inhomogeneity is the origin of the double peak in resistivity behavior of their samples. Sun et al [29] have shown that the oxygenation inhomogeneity leads to a double peak behavior. In these cases, the compositional disorder occurs in the scale of the whole sample and not in each grain as in the case of small grain size samples.…”
Section: Resultsmentioning
confidence: 98%
“…According to Sun et al's [30] work, when fabricating the sample of La 0.72−x Gd x Ca 0.3 Mn y O 3+δ by solid-state reaction, the different activities of La 2 O 3 and La(OH) 3 leaded to inhomogeneous distribution of oxygen content in the compound, which caused two peak of the ρ -T curves. Wu et al [19] also confirmed that the double peak shown in ρ -T curves of La 0.9 MnO 3+δ were closely related to the oxygen content.…”
Section: Resultsmentioning
confidence: 98%
“…-Other authors [42] deliberately used a mixture of La(OH) 3 and La 2 O 3 as source of lanthanum and obtained double peaks. But our La 2 O 3 was calcined before use.…”
Section: Resultsmentioning
confidence: 99%